The design and synthesis of novel spirocyclic heterocyclic sulfone ROMK inhibitors as diuretics. Issue 4 (15th February 2017) - Chobanian, Harry R.; Guo, Yan; Pio, Barbara; Tang, Haifeng; Teumelsan, Nardos; Clements, Matthew; Frie, Jessica; Ferguson, Ronald; Guo, Zach; Thomas-Fowlkes, Brande S.; Felix, John P.; Liu, Jessica; et al.
Graphical abstract: Abstract: A spirocyclic class of ROMK inhibitors was developed containing a structurally diverse heterocyclic sulfone moiety and spirocyclic core starting from lead1 . These compounds not only displayed exquisite ROMK potency but significantly improved selectivity over hERG. The lead compounds were found to have favorable pharmacokinetic properties and displayed robust diuretic, natriuretic and blood pressure lowering effects in spontaneously hypertensive rats.